Metal-clad laminates, printed wiring boards and semiconductor packages

JP7635894B2Active Publication Date: 2025-02-26RESONAC CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024541027
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-12-07
Filing Date
2023-12-06
Publication Date
2025-02-26
Estimated Expiration
2043-12-06

AI Technical Summary

Benefits of technology

【0006】 本開示によれば、半導体パッケージの反り量のバラつきを低減することができ、且つ、寸法変化率のバラツキが小さい金属張り積層板を提供すること、並びに、プリント配線板及び半導体パッケージを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635894000002
    Figure 0007635894000002
  • Figure 0007635894000003
    Figure 0007635894000003
  • Figure 0007635894000004
    Figure 0007635894000004
Patent Text Reader

Abstract

Provided is, inter alia, a metal-clad laminate that exhibits low variation in dimension change rate and that makes it possible to reduce any variation in the amount of warping in a semiconductor package. This metal-clad laminate comprises a metal foil, and a cured article of one or more prepregs, the average thickness of the metal-clad laminate as measured in accordance with the method described below using a laser displacement sensor being 400 μm or greater, and the value calculated using formula (1) being 0.70% or lower. Formula (1): (average value of standard deviation of thickness derived according to measurement method)×100 / (average thickness of metal-clad laminate). (Method for measuring thickness of metal-clad laminate) To measure the thickness, four measurement boards, each of which is sized to 60 mm long by 60 mm wide in a planar direction, are cut out from a desired location in the metal-clad laminate. The start point and end point in measurement are not positioned at the ends of the metal-clad laminate, and the thickness is measured at 1-mm intervals on two diagonal lines. The standard deviation for each of the four measurement boards is derived from the thickness of all measured points, after which the average value of the standard deviation of the thickness in each of the four measurement boards is derived. Furthermore, the average thickness of all measured points in the four measurement boards is calculated, and the result of calculation is employed as the average thickness of the metal-clad laminate. The details are as set forth in the description.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a metal-clad laminate, a printed wiring board, and a semiconductor package. [Background technology]

[0002] With the recent trend toward higher density and finer semiconductor packages, there is a need for miniaturization technology for package circuits, as well as miniaturization of solder bumps connecting semiconductor chips to organic substrates or interposers. In addition, printed wiring boards used in semiconductor packages are required to have low warpage, improved dimensional stability, and impedance control in order to ensure high reliability in a finer structure. Focusing on low warpage, attempts have been made to reduce warpage of printed wiring boards or semiconductor packages by studying the insulating resin material of the laminate, such as by bringing the thermal expansion coefficient of the insulating resin material of the laminate closer to that of the silicon chip, adjusting the elastic modulus, etc. For example, for the purpose of reducing the warpage, Patent Document 1 discloses a prepreg formed from a resin composition containing a specific low elastic component and a woven fabric substrate, and Patent Document 2 discloses a resin composition containing a specific maleimide compound and a specific silicone compound, and a prepreg formed using the resin composition. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2015-189834 A [Patent Document 2] International Publication No. 2012 / 099134 Summary of the Invention [Problem to be solved by the invention]

[0004] As described in Patent Documents 1 and 2, reducing the amount of warpage itself in semiconductor packages is important, but further investigation has revealed that reducing "variation in the amount of warpage" is also important from the perspective of ensuring the reliability of semiconductor packages. Therefore, there is a strong demand for the development of new technology that can reduce variation in the amount of warpage in semiconductor packages. In addition, when manufacturing a semiconductor package, there is a process in which a build-up material is laminated multiple times on a laminate and then heated and cured. If the dimensional change rate of the laminate after this heat curing process varies greatly, there is a concern that the pattern formed on the solder resist layer provided on the outermost layer will become misaligned, reducing the connection area of ​​the solder bumps that connect to the semiconductor chip, which may result in a deterioration in reliability. Therefore, in order to ensure high reliability, it is desirable for the dimensional change rate of the laminate when heated to vary as little as possible. Therefore, an object of the present disclosure is to provide a metal-clad laminate that can reduce variation in the amount of warping of a semiconductor package and has small variation in the rate of dimensional change, and to provide a printed wiring board and a semiconductor package. [Means for solving the problem]

[0005] As a result of extensive research, the present inventors have found that the above object can be achieved by the present disclosure. The present disclosure includes the following [1] to [6]. [1] A metal-clad laminate having a metal foil and one or more cured prepregs, A metal-clad laminate having an average thickness of 400 μm or more as measured according to the following method using a laser displacement meter, and a value calculated from the following formula (1) of 0.70% or less. Formula (1): (Average value of standard deviation of thickness obtained by the measurement method below) × 100 / (Average thickness of metal-clad laminate) (Method of measuring thickness of metal-clad laminate) The thickness is measured by cutting out four measurement substrates, each 60 mm long and 60 mm wide, from any point on the metal-clad laminate. Measurements are taken at 1 mm intervals on two diagonals, with the start and end points of the measurement not being located at the ends of the metal-clad laminate. For each of the four test substrates, the standard deviation is calculated from the thicknesses at all the measured points, and then the average value of the standard deviations of the thicknesses for each of the four test substrates is calculated. Furthermore, the average thickness of all the measured points for the four test substrates is calculated, and this is regarded as the average thickness of the metal-clad laminate. [2] The metal-clad laminate according to the above [1], wherein the average value of the standard deviation of the thickness in the formula (1) is 0.1 to 10.0 μm. [3] The metal-clad laminate according to the above [1] or [2], wherein the prepreg is a prepreg containing a fiber base material having a thickness of 40 μm or more and a thermosetting resin composition. [4] The metal-clad laminate according to any one of the above [1] to [3], wherein the metal foil has a thickness of 1 to 200 μm. [5] A printed wiring board comprising the metal-clad laminate according to any one of [1] to [4] above. [6] A semiconductor package comprising the printed wiring board according to [5] above and a semiconductor element. Effect of the Invention

[0006] According to the present disclosure, it is possible to provide a metal-clad laminate that can reduce variation in the amount of warping of a semiconductor package and has small variation in the rate of dimensional change, as well as to provide a printed wiring board and a semiconductor package. [Brief description of the drawings]

[0007] [Figure 1] FIG. 2 is a schematic diagram for explaining a method for measuring the thickness of the metal-clad laminate of the present embodiment. [Diagram 2] FIG. 2 is a perspective view of an example of a measurement site of a non-contact and clamping type laser displacement meter used in measuring the thickness of the metal-clad laminate of this embodiment. [Diagram 3]2 is a schematic diagram of an example of a sensor head of a laser displacement meter used in measuring the thickness of the metal-clad laminate of the present embodiment. FIG. [Figure 4] FIG. 2 is a cross-sectional schematic diagram showing one embodiment of a prepreg used in the metal-clad laminate of the present embodiment. [Diagram 5] FIG. 2 is a cross-sectional view of a prepreg for explaining the thickness of a fiber base material and the resin thickness on the front and back sides. [Figure 6] 1 is a surface observation image converted into black and white mode and used to calculate the abundance ratio of the impregnated region in the prepreg produced in Example 1. [Figure 7] FIG. 2 is a schematic diagram illustrating how to cut out four measurement substrates (N1 to N4) from predetermined positions at the four corners of a copper-clad laminate when measuring the thickness of the copper-clad laminate in the examples and comparative examples. [Figure 8] FIG. 2 is a schematic diagram for explaining how to cut out four evaluation substrates from a copper-clad laminate when evaluating the variation in the dimensional change rate of the copper-clad laminate in the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] One embodiment of the present disclosure will be described in detail below, but the present disclosure is not limited to the embodiment described below. In the numerical ranges described in the present disclosure, the lower limit or upper limit of the numerical range may be replaced with the values ​​shown in the examples. In addition, the lower limit and upper limit of a numerical range may be arbitrarily combined with the lower limit or upper limit of another numerical range. In the expression of a numerical range "AA to BB", the numerical values ​​AA and BB at both ends are included in the numerical range as the lower limit and upper limit, respectively. In the present disclosure, for example, the description "10 or more" means 10 and a numerical value exceeding 10, and the same applies when the numerical values ​​are different. Also, for example, the description "10 or less" means 10 and a numerical value less than 10, and the same applies when the numerical values ​​are different. In addition, unless otherwise specified, each component and material exemplified in the present disclosure may be used alone or in combination of two or more. In the present disclosure, the content of each component in the thermosetting resin composition means the total amount of the multiple substances present in the thermosetting resin composition when multiple substances corresponding to each component are present in the thermosetting resin composition, unless otherwise specified.

[0009] In the present disclosure, the term "resin component" is defined as all components among the solid contents constituting the thermosetting resin composition, excluding inorganic compounds such as inorganic fillers described below, and flame retardants and flame retardant assistants. In this disclosure, "solid content" refers to components other than the solvent, and components that are liquid at 25°C are also considered to be solid content. The expression "containing XX (component)" described in the present disclosure may mean that XX (component) is contained in a reacted state when XX (component) is reactive, or may mean that XX (component) is simply contained as is, or may include both of these aspects. Any combination of the descriptions in this disclosure is also included in this disclosure and this embodiment.

[0010] [Metal-clad laminate] The present disclosure relates to a metal-clad laminate having a metal foil and one or more cured prepregs, The present invention relates to a metal-clad laminate having an average thickness of 400 μm or more as measured according to the following method using a laser displacement meter, and a value calculated from the following formula (1) of 0.70% or less. Formula (1): (Average value of standard deviation of thickness obtained by the method below) × 100 / (Average thickness of metal-clad laminate) (Method of measuring thickness of metal-clad laminate) The thickness is measured by cutting out four measurement substrates, each 60 mm long and 60 mm wide in the surface direction, from any point on the metal-clad laminate. As shown in Figure 1, measurements are taken at 1 mm intervals on two diagonals, with the start and end points of the measurement not being located at the ends of the metal-clad laminate. For each of the four measurement boards, the standard deviation is calculated from the thickness at all measured points, and then the average value of the standard deviations of the thicknesses for each of the four measurement boards (the sum of the standard deviations of the thicknesses of each of the four measurement boards / 4) is calculated. Furthermore, the average thickness of all measured points for the four measurement boards is calculated, and this is regarded as the average thickness of the metal-clad laminate. The order of measurements on the two diagonal measurement lines is not particularly limited, and measurements may be taken on either diagonal line. However, if it is not possible to cut out four measurement boards measuring 60 mm long x 60 mm wide due to the size of the metal-clad laminate, the maximum number of boards measuring 60 mm long x 60 mm wide will be used instead. If the surface size of the metal-clad laminate is a square or rectangle with a length of 60 mm or less or a width of 60 mm or less, it is used as the measurement substrate. In this case, since it is not possible to prepare four measurement substrates, the "average standard deviation of thickness" in formula (1) is substituted with the "standard deviation of thickness" of the one measurement substrate, and the "average thickness of the metal-clad laminate" in formula (1) is substituted with the "average thickness" of the one measurement substrate. The lower limit of the size of the measurement substrate in the surface direction is 20 mm or more in length×20 mm or more in width.

[0011] When the metal-clad laminate of this embodiment has an average thickness of 400 μm or more measured according to the above method using a laser displacement meter, the variation in the amount of warpage of the semiconductor package can be effectively reduced by making the value calculated from the formula (1) 0.70% or less. In addition, the metal-clad laminate of this embodiment can be said to have a high degree of freedom in designing the insulating resin material. Furthermore, in the case of the metal-clad laminate of this embodiment, the variation in the dimensional change rate is small when a heat treatment is performed after the metal foil is removed by etching in a plurality of evaluation boards cut out from any location. The variation in the dimensional change rate of the metal-clad laminate is preferably 0.005% or less, more preferably 0.004% or less, even more preferably 0.003% or less, particularly preferably 0.002% or less, and most preferably 0.001% or less. The following method can be adopted as a method for measuring the variation in the dimensional change rate, and more specifically, the method described in the Examples is adopted. For example, after preparing two copper-clad laminates, two pieces each of which are cut out to 340 mm x 250 mm (total of four pieces) are used as evaluation boards, and a total of four reference holes are made in the four evaluation boards at positions 1 cm vertically and 1 cm horizontally from the four corners, and the distance between adjacent holes is measured using a CNC image measuring device, and the value is taken as the "reference dimension". The copper foil is removed from the evaluation board by etching. Next, the evaluation board from which the copper foil has been removed is heated in air at 180°C for 1 hour, then cooled to 25°C, and heated again in air at 180°C for 1 hour. The distance between adjacent holes is then measured using the same method as above, and this value is taken as the "dimension after heating." From each of the obtained dimensions, the dimensional change rate after heating for the four evaluation boards is calculated based on the following formula. Dimensional change rate (%) = (dimension after heating - reference dimension) x 100 / reference dimension After calculating the dimensional change rate of the four evaluation substrates (two data points in the vertical direction and two data points in the horizontal direction per substrate), the standard deviation (σ value) is calculated and this value is regarded as the variation in the dimensional change rate.

[0012] The average thickness of the metal-clad laminate may be 400 to 2,500 μm, 450 to 2,000 μm, 500 to 1,800 μm, 550 to 1,600 μm, 700 to 1,600 μm, or 1,000 to 1,600 μm.

[0013] From the viewpoint of reducing the variation in the amount of warpage of the semiconductor package, the average value of the standard deviation of the thickness of the metal-clad laminate is preferably 0.1 to 10.0 μm, more preferably 0.1 to 8.0 μm, and even more preferably 0.1 to 6.0 μm, and may be 0.1 to 4.0 μm or 0.1 to 2.5 μm. The lower limit of the average value of the standard deviation of the thickness of the metal-clad laminate is not particularly limited, but may be 0.3 μm or more, or may be 0.5 μm or more.

[0014] In the metal-clad laminate of this embodiment, from the viewpoint of reducing the variation in the dimensional change rate of the metal-clad laminate and reducing the variation in the warpage amount of the semiconductor package, the value calculated from the formula (1) is 0.70% or less, preferably 0.65% or less, more preferably 0.60% or less, even more preferably 0.55% or less, particularly preferably 0.50% or less, most preferably 0.45% or less, may be 0.40% or less, may be 0.35% or less, may be 0.30% or less, may be 0.25% or less, may be 0.20% or less, or may be 0.15% or less. The lower limit of the value is not particularly limited, but may be 0.01% or more, may be 0.03% or more, or may be 0.05% or more. That is, the value may be 0.01 to 0.70%, may be 0.01 to 0.65%, may be 0.01 to 0.60%, may be 0.01 to 0.55%, may be 0.01 to 0.50%, may be 0.03 to 0.50%, or may be 0.05 to 0.50%.

[0015] The thickness of the metal-clad laminate of this embodiment is measured by measuring the thickness of the measurement substrate using a non-contact and clamping type laser displacement meter as shown in FIG. 2 (preferably a non-contact and clamping type laser displacement meter) under the conditions of a measurement speed of 10 mm / sec, a measurement range of 300 μm diameter, and a repeatability of 0.3 μm or less. More specifically, the measurement is performed by the method described in the examples. Here, the repeatability refers to the degree of variation when measurements are repeatedly taken at a fixed point on the measurement object. The smaller the repeatability, the smaller the degree of variation in values ​​due to repeated measurements. The laser displacement meter measures thickness by applying laser light from both sides of the object and detecting the distance from the reflected light to each side. The multi-color laser coaxial displacement meter "CL-3000" series manufactured by Keyence Corporation can be used as the laser displacement meter. The laser displacement meter is less susceptible to the influence of slight warping of the metal-clad laminate itself when measuring thickness, and has high measurement accuracy.

[0016] In the metal-clad laminate of this embodiment, the number of prepregs may be 1 to 25, 2 to 20, 5 to 18, 8 to 16, or 10 to 14. Examples of the metal foil in the metal-clad laminate include copper foil, aluminum foil, tin foil, tin-lead alloy (solder) foil, and nickel foil. In addition, a three-layer composite foil having an intermediate layer of nickel, nickel-phosphorus, nickel-tin alloy, nickel-iron alloy, lead, or lead-tin alloy, and a copper layer of 0.5 to 15 μm and a copper layer of 10 to 300 μm on both sides of the intermediate layer, and a two-layer composite foil in which aluminum and copper foil are combined can be used. The metal foil is preferably copper foil, the three-layer composite foil, or the two-layer composite foil, and more preferably copper foil. When the metal foil is copper foil, the metal-clad laminate is called a copper-clad laminate. The thickness of the metal foil can be a thickness generally used for metal-clad laminates, and is preferably 1 to 200 μm, more preferably 3 to 100 μm, further preferably 5 to 50 μm, particularly preferably 5 to 25 μm, and most preferably 7 to 18 μm.

[0017] (Metal-clad laminate manufacturing method) The metal-clad laminate of this embodiment can be produced by placing metal foil on both sides of a single prepreg or on both sides of a prepreg laminate containing one or more prepregs, and then press-molding the laminate. Specific methods of press-molding include, for example, a method of press-molding in a vacuum press under conditions of a degree of vacuum of preferably 300 kPa or less, more preferably 100 kPa or less, a temperature of preferably 130 to 350°C, more preferably 150 to 300°C, and even more preferably 170 to 250°C, and a pressure of preferably 0.5 to 10 MPa, more preferably 1 to 5 MPa. There are no particular limitations on the method for producing the metal-clad laminate of this embodiment, i.e., a metal-clad laminate having an average thickness measured according to the above method of 400 μm or more and a value calculated from the above formula (1) of 0.70% or less, and it can also be produced, for example, by using the prepreg described below.

[0018] (Prepreg) The prepreg is not particularly limited, but may be a prepreg containing a fiber base material having a thickness of 40 μm or more and a thermosetting resin composition, the fiber base material having an impregnated region and an unimpregnated region of the thermosetting resin composition, and a surface waviness (Wa) of 5.0 μm or less. The metal-clad laminate of this embodiment can be manufactured using this prepreg. Note that the fact that the fiber base material has an impregnated region and an unimpregnated region of the thermosetting resin composition refers only to the prepreg, that is, the prepreg in the B-stage state, and does not refer to the cured product of the prepreg. The surface waviness (Wa) is the arithmetic mean height (Wa) that can be obtained from a waviness curve according to ISO 4287 (1997). JIS B 0601 (2001) may be used instead of ISO 4287 (1997). The surface waviness (Wa) can be measured as follows. Using a shape analysis laser microscope "VK-X100" (manufactured by Keyence Corporation), shape measurement is performed automatically using an observation application to obtain a waviness curve conforming to ISO 4287 (1997) or JIS B 0601 (2001). For the obtained waviness curve, a surface roughness analysis is performed using an analysis application to calculate the surface waviness (Wa). Here, the waviness curve is a curve obtained by applying a phase compensation high-pass filter λc (λc = 80 μm) to the cross-sectional curve and removing wavelengths less than 80 μm from the cross-sectional curve. The analysis range is 1,000 μm x 1,000 μm. Unless otherwise specified, the surface waviness (Wa) of the prepreg refers to the surface waviness of at least one surface of the prepreg, and the "surface" refers to the surface that will be overlapped when a plurality of prepregs are laminated to produce a metal-clad laminate, or the surface opposite thereto. For example, the surface waviness (Wa) of at least one surface of the prepreg is preferably 5.0 μm or less, and from the viewpoint of the thickness accuracy of the metal-clad laminate, it is more preferable that the surface waviness (Wa) of both surfaces of the prepreg is 5.0 μm or less.

[0019] The prepreg has a surface waviness (Wa) of 5.0 μm or less, even though it uses a "fiber base material having a thickness of 40 μm or more" which has a larger surface waviness than a thin fiber base material. This is achieved by adopting a method of "deliberately providing an area not impregnated with the thermosetting resin composition in the fiber base material of the prepreg". This method is generally difficult to adopt, considering the conventional technical common sense that the generation of voids is suppressed by increasing the impregnation rate of the thermosetting resin composition into the fiber base material as much as possible during the prepreg manufacturing stage. It was found that the metal-clad laminate of this embodiment can be manufactured by using the prepreg. The mechanism by which the metal-clad laminate of this embodiment can be manufactured using the prepreg is not clear, but is considered as follows. For example, as shown in FIG. 4, when the resin film is impregnated into the fiber base material, a region in which the thermosetting resin composition is not impregnated is intentionally provided in the fiber base material, so that the layer of the thermosetting resin composition near the surface (hereinafter, abbreviated as resin layer) exists without following the waviness of the glass cloth. As a result, the large waviness of the fiber base material having a thickness of 40 μm or more is difficult to be reflected on the surface of the prepreg, and the surface waviness (Wa) of the prepreg becomes 5.0 μm or less. Then, by press molding using the prepreg with a surface waviness (Wa) of 5.0 μm or less, the thickness of the metal-clad laminate is suppressed from varying due to the small surface waviness (Wa) of the prepreg, and the metal-clad laminate of this embodiment can be manufactured.

[0020] In the prepreg, an unimpregnated region of the thermosetting resin composition is provided in the fiber base material. During press molding to produce the metal-clad laminate, the thermosetting resin composition flows in the thickness direction and into the unimpregnated region, thereby sufficiently suppressing the generation of voids in the metal-clad laminate.

[0021] From the above viewpoints, the surface waviness (Wa) of the prepreg is preferably 5.0 μm or less, more preferably 3.0 μm or less, and even more preferably 1.0 μm or less. The lower limit of the surface waviness (Wa) of the prepreg is not particularly limited, but may be 0.01 μm or more, 0.1 μm or more, or 0.2 μm or more. In other words, the surface waviness (Wa) of the prepreg may be 0.01 to 5.0 μm, 0.1 to 3.0 μm, or 0.2 to 1.0 μm.

[0022] (Regarding the presence of regions in the fiber substrate that are not impregnated with the thermosetting resin composition) As described above, the prepreg has an impregnated region and an unimpregnated region of the thermosetting resin composition in the fiber base material, and is particularly characterized by having the unimpregnated region. The presence of the unimpregnated region can be confirmed by determining the ratio of the impregnated region of the thermosetting resin composition in the fiber base material. In other words, if the ratio of the impregnated region is not 100%, it means that the prepreg has an unimpregnated region. The method for determining the ratio of the impregnated region of the thermosetting resin composition in the fiber base material can be, for example, the following calculation method. From the viewpoint of the thickness accuracy of the metal-clad laminate, the ratio of the impregnated region determined based on the following calculation method is not particularly limited, but may be 25 to 98%, 30 to 98%, 35 to 97%, 40 to 95%, 35 to 90%, 40 to 85%, 40 to 75%, 45 to 98%, 50 to 98%, 60 to 97%, 65 to 97%, or 75 to 97%. When the ratio is 98% or less, the effect of improving the thickness accuracy of the metal-clad laminate tends to be large, and when it is 95% or less, this tendency is even greater. Furthermore, when the presence ratio is 25% or more, powder falling off of the thermosetting resin composition from the prepreg is suppressed, which tends to provide the secondary effect of good handleability.

[0023] -Calculation method- A surface observation image is obtained by observing the surface of the prepreg using an optical microscope at a magnification of 50. The observation conditions are those described in detail in the Examples from the viewpoint of photographing in an appropriate brightness. The obtained surface observation image is converted to black and white mode by image editing software, and then saved in BMP (Microsoft Windows Bitmap Image) format. Next, the black and white mode surface observation image saved in BMP format is converted to RGB (Red, Green, Blue) values ​​for each pixel by image conversion software, and then saved in CSV (comma-separated values) format. The RGB data saved in CSV format is pasted into Microsoft Excel (Microsoft Corporation), and the areas of the black parts (RGB value = 255) and the white parts (RGB value = 0) are calculated. From these values, the area ratio of the black parts to the total of the black parts and the white parts is calculated. The area ratio of the black parts thus obtained is regarded as the abundance ratio of the impregnated region. As the image editing software, for example, "Microsoft Paint" (manufactured by Microsoft Corporation) can be used. Furthermore, as the image conversion software, for example, free software "bmp2csv" can be used. In the above observation, when the surface observation image taken at a moderate brightness is converted to a black and white mode, the surface where the unimpregnated region of the thermosetting resin composition exists below the observation surface is a void portion that is easily reflective of light, and is therefore represented as "white", and the other surfaces are represented as "black". Here, when taking a surface observation image, it is preferable to adjust the exposure time during surface photography within a range of 60 to 100 ms, so that the image can be taken at a moderate brightness that can fully reflect the impregnated and unimpregnated regions. In the surface observation image of the prepreg, the areas in order of intensity of color are "areas in the resin layer where no glass cloth exists", "areas in which the glass cloth is sufficiently impregnated with the thermosetting resin composition", and "areas in which the glass cloth is insufficiently impregnated with the thermosetting resin composition". In this embodiment, the "areas in the resin layer where no glass cloth exists" are also included in the impregnated area. If the surface observation image is too bright, not only the parts where the resin is not sufficiently impregnated into the glass cloth but also the parts where the resin is sufficiently impregnated into the glass cloth tend to be shown in white in the surface observation image in the black and white mode, and if the image is even brighter, the surface observation image in the black and white mode tends to be white overall. On the other hand, if the surface observation image is too dark, the surface observation image in the black and white mode tends to be black overall, making it difficult to reflect the presence of unimpregnated areas. Therefore, it is preferable to take the image at a moderate brightness. As an example of converting a surface observation image taken at a moderate brightness into a black and white mode, the surface observation image converted into the black and white mode obtained in Example 1 is shown in FIG. 6. In addition, the area ratio of the white areas to the total area of ​​the white and black areas can be easily calculated by using the COUNTIF function in Microsoft Excel (Microsoft Corporation).

[0024] (Relationship between the thickness of resin protruding from the fiber base material on the front and back of the prepreg) The prepreg is not particularly limited, but by setting the difference in thickness of the resin protruding from the fiber substrate on the front and back of the prepreg to preferably 0 to 10 μm, it is possible to suppress warping of the prepreg itself and reduce the amount of warping of the metal-clad laminate. In the present disclosure, the thickness of the thermosetting resin composition protruding from the fiber substrate on the front and back of the prepreg is sometimes referred to as the "resin thickness", and the difference between the resin thickness on the front surface of the prepreg and the resin thickness on the back surface of the prepreg is sometimes referred to as the "resin thickness difference". From the viewpoint of reducing the amount of warping of the metal-clad laminate, the difference in resin thickness is more preferably 0 to 7 μm, further preferably 0 to 5.5 μm, particularly preferably 0 to 3.5 μm, and most preferably 0 to 2.5 μm. The lower limit of the difference in resin thickness may be 0.1 μm, 0.3 μm, 0.5 μm, or 0.8 μm. The resin thickness is the shortest distance from a resin end on the front or back of the prepreg to the glass cloth in an image of a cross section of the prepreg observed with a metallurgical microscope as shown in Fig. 5. For convenience, the thermosetting resin composition impregnated in the fiber base material is not shown in Fig. 5. By reducing the difference in the thickness of the resin protruding from the fiber base material as described above, the difference in the amount of thermal expansion between the front and back of the prepreg during press molding is reduced, so it is believed that the metal-clad laminate tends to be less prone to warping when made into a metal-clad laminate. Reducing the amount of warping of the metal-clad laminate contributes to improving the connection reliability of printed wiring boards and semiconductor packages.

[0025] (Textile base material) As the fiber substrate having a thickness of 40 μm or more contained in the prepreg, a well-known one used in various laminates for electrical insulating materials can be used. Examples of the material of the fiber substrate include natural fibers such as paper and cotton linters; inorganic fibers such as glass fibers and asbestos; organic fibers such as aramid, polyimide, polyvinyl alcohol, polyester, tetrafluoroethylene, and acrylic; and mixtures thereof. Among these, inorganic fibers are preferred from the viewpoint of flame retardancy, and glass fibers are more preferred. Furthermore, examples of glass fibers include glass cloth using E glass, C glass, D glass, S glass, etc.; glass cloth in which short fibers are bonded with an organic binder; and a mixture of glass fibers and cellulose fibers. Among these, glass cloth using E glass is preferred as the glass fiber. The shape of the fiber substrate is not particularly limited, and may be woven fabric, nonwoven fabric, roving, chopped strand mat, surfacing mat, etc. Among these, when it is woven fabric, the effect of improving the thickness precision of the metal-clad laminate tends to be more remarkable. In other words, it is more preferable to use glass woven fabric (also called glass cloth) as the fiber substrate. The material and shape can be appropriately selected according to the intended use and performance of the molded product. As the fiber substrate, one type may be used alone, or two or more types of materials and two or more types of shapes may be used in combination as necessary. The fiber substrate may be a fiber substrate made of one layer or a fiber substrate made of multiple layers. The fiber substrate made of one layer means a fiber substrate made of only entangled fibers, and when there is a fiber substrate that is not entangled, it is classified as a fiber substrate made of multiple layers. The material and shape of the fiber substrate of two or more layers may be the same or different.

[0026] (Thickness of fiber base material) The thickness of the fiber base material contained in the prepreg (see FIG. 5) is set to "40 μm or more," which has been found by the inventors' investigations to "tend to deteriorate the thickness accuracy of the metal-clad laminate." The thickness of the fiber base material may be 40 to 120 μm, 45 to 120 μm, 50 to 120 μm, 55 to 120 μm, 60 to 120 μm, 70 to 120 μm, 80 to 110 μm, or 90 to 110 μm. In addition, from the viewpoint of improving the impregnation of the thermosetting resin composition into the fiber base material and tending to improve the heat resistance and insulation reliability of the cured product of the prepreg, the thickness of the fiber base material is preferably less than 100 μm, and may be 40 μm or more and less than 100 μm, 40 to 97 μm, 50 to 97 μm, 60 to 97 μm, 70 to 97 μm, or 80 to 95 μm. The larger the thickness of the fiber base material, the larger the surface waviness of the fiber base material itself tends to be, so that the thickness accuracy of the metal-clad laminate generally decreases. However, by using the prepreg, even if the thickness of the fiber base material is large as described above, the surface waviness (Wa) of the prepreg is suppressed to be small, and as a result, the thickness accuracy of the metal-clad laminate is increased, making it easier to manufacture the metal-clad laminate of this embodiment. In the present disclosure, the thickness of the fiber base material is the thickness at the portion shown in FIG. 5, and is the average value of values ​​obtained by measuring five arbitrary portions of the fiber base material with a micrometer.

[0027] Incidentally, the metal-clad laminate of this embodiment can be manufactured using a plurality of prepregs as described above, and may include three or more fiber substrates. As described above, the metal-clad laminate of this embodiment has high thickness accuracy, so there is no need to perform smoothing treatment such as polishing and roll pressing on the surface of the cured prepreg, and is excellent in productivity. Therefore, in a metal-clad laminate including three or more fiber substrates, the outermost fiber substrate is not scraped by smoothing treatment, and the thickness of the outermost fiber substrate on at least one surface side of the metal-clad laminate tends to be within the range of 0.6 to 1.3 times the thickness of the fiber substrate adjacent to the fiber substrate, preferably within the range of 0.7 to 1.3 times, more preferably within the range of 0.8 to 1.2 times, and even more preferably within the range of 0.9 to 1.1 times. It is preferable that the thickness of the outermost fiber substrate on both surfaces of the metal-clad laminate is within the above range with respect to the thickness of the adjacent fiber substrate.

[0028] (Prepreg thickness) The thickness of the prepreg may be appropriately determined depending on the thickness of the fiber base material, etc., and may be 50 to 300 μm, 50 to 250 μm, 55 to 200 μm, 60 to 180 μm, 70 to 150 μm, or 80 to 130 μm. Here, the thickness of the prepreg refers to the thickness of one prepreg. When the thickness of the prepreg is equal to or greater than the lower limit, the effect of reducing surface waviness according to this embodiment tends to be significantly obtained. When the thickness of the prepreg is equal to or less than the upper limit, the generation of voids after the production of the laminate tends to be suppressed in this embodiment. In the present disclosure, the thickness of the prepreg is the average value of values ​​obtained by measuring any five points with a Digimatic indicator.

[0029] <Thermosetting resin composition> The prepreg is prepared by impregnating a fiber substrate having a thickness of 40 μm or more with a thermosetting resin composition and then semi-curing (B-staging). In this disclosure, B-staging refers to bringing the material into the B-stage state defined by JIS K6900 (1994). The thermosetting resin composition contains at least a thermosetting resin. The components contained in the thermosetting resin composition are not particularly limited, but preferably contain at least one selected from the group consisting of a curing agent, a curing accelerator, an inorganic filler, an organic filler, a coupling agent, a leveling agent, an antioxidant, a flame retardant, a flame retardant assistant, a thixotropy imparting agent, a thickener, a flexible material, a surfactant, and a photopolymerization initiator, in addition to the thermosetting resin. Each component contained in the thermosetting resin composition will be briefly described below.

[0030] (thermosetting resin) Examples of the thermosetting resin include epoxy resin, polyimide resin, maleimide resin, modified maleimide resin, phenol resin, polyphenylene ether resin, bismaleimide triazine resin, cyanate resin, isocyanate resin, benzoxazine resin, oxetane resin, amino resin, unsaturated polyester resin, allyl resin, dicyclopentadiene resin, silicone resin, triazine resin, melamine resin, etc. Examples of the modified maleimide resin include a reaction product of a maleimide compound having at least two N-substituted maleimide groups and at least one compound selected from the group consisting of monoamine compounds and diamine compounds. Here, the maleimide resin does not include the modified maleimide resin. In addition, the thermosetting resin is not particularly limited to these, and known thermosetting resins can be used. The thermosetting resin may be used alone or in combination of two or more types. Among these, from the viewpoints of moldability and electrical insulation, it is preferable to contain, as the thermosetting resin, at least one selected from the group consisting of epoxy resins, polyimide resins, maleimide resins, modified maleimide resins, cyanate resins, polyphenylene ether resins, and bismaleimide triazine resins, it is more preferable to contain at least one selected from the group consisting of epoxy resins, polyimide resins, maleimide resins, modified maleimide resins, cyanate resins, and polyphenylene ether resins, and it is even more preferable to contain at least one selected from the group consisting of epoxy resins, maleimide resins, and modified maleimide resins.

[0031] The epoxy resin is preferably an epoxy resin having two or more epoxy groups in one molecule. Here, the epoxy resin is classified into glycidyl ether type epoxy resin, glycidyl amine type epoxy resin, glycidyl ester type epoxy resin, etc. Among these, glycidyl ether type epoxy resin is preferable. Epoxy resins are classified into various epoxy resins according to the difference in the main skeleton. For example, the above-mentioned types of epoxy resins are further classified into bisphenol-type epoxy resins, alicyclic epoxy resins, aliphatic chain epoxy resins, novolac-type epoxy resins, stilbene-type epoxy resins, naphthalene skeleton-containing epoxy resins, biphenyl-type epoxy resins, xylylene-type epoxy resins, dihydroanthracene-type epoxy resins, etc. One type of epoxy resin may be used alone, or two or more types may be used in combination from the viewpoints of insulation reliability and heat resistance. The epoxy resin may be a novolac type epoxy resin or a phenol novolac type epoxy resin.

[0032] In the thermosetting resin composition, the content of the thermosetting resin is preferably 10 to 100 mass%, more preferably 20 to 95 mass%, further preferably 30 to 95 mass%, particularly preferably 30 to 90 mass%, most preferably 30 to 70 mass%, and may be 35 to 55 mass%, based on the total solid content.

[0033] (hardening agent) For example, when the thermosetting resin contains an epoxy resin, the curing agent may be a phenol-based curing agent, a cyanate ester-based curing agent, an acid anhydride-based curing agent, an amine-based curing agent, or an active ester group-containing compound. When the thermosetting resin contains a resin other than an epoxy resin, a known curing agent for the thermosetting resin may be used. The curing agent may be used alone or in combination of two or more types.

[0034] The phenol-based curing agent is not particularly limited, but preferred examples thereof include cresol novolac type phenolic resins, biphenyl aralkyl type phenolic resins, phenol novolac type phenolic resins, naphthylene ether type phenolic resins, and triazine skeleton-containing phenolic resins.

[0035] The cyanate ester-based curing agent is not particularly limited, but examples thereof include bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), and the like. The acid anhydride curing agent is not particularly limited, but examples thereof include phthalic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, and pyromellitic anhydride. The amine-based curing agent is not particularly limited, but examples thereof include aliphatic amines such as triethylenetetramine and tetraethylenepentamine; and aromatic amines such as 4,4'-diaminodiphenylmethane. Moreover, as the hardener, urea resin or the like can also be used.

[0036] When the thermosetting resin composition contains a curing agent, the content thereof is preferably 20 to 200 parts by mass, more preferably 20 to 150 parts by mass, and further preferably 30 to 100 parts by mass, based on 100 parts by mass of the thermosetting resin. In addition, when the thermosetting resin composition contains a curing agent, the content may be expressed by the functional group equivalent. Specifically, the content of the curing agent is preferably an amount that satisfies the formula: (mass of thermosetting resin / functional group equivalent) ≒ (mass of curing agent / functional group equivalent capable of reacting with thermosetting resin) × constant C. The constant C varies depending on the type of functional group of the curing agent, and is preferably 0.8 to 1.2 when the functional group is a phenolic hydroxyl group, preferably 0.2 to 0.4 when the functional group is an amino group, and preferably 0.3 to 0.6 when the functional group is an active ester group. When the thermosetting resin contains an epoxy resin, the above formula becomes (mass of epoxy resin / epoxy group equivalent)≒(mass of curing agent / functional group equivalent capable of reacting with epoxy group)×constant C.

[0037] (Cure accelerator) As the curing accelerator, a general curing accelerator used for curing the thermosetting resin can be used. For example, when the thermosetting resin contains an epoxy resin, the curing accelerator may be an imidazole compound and its derivatives; a phosphorus-based compound; a tertiary amine compound; a quaternary ammonium compound, etc. From the viewpoint of accelerating the curing reaction, an imidazole compound and its derivatives are preferred. Specific examples of the imidazole compound and its derivatives include imidazole compounds such as 2-methylimidazole, 2-ethylimidazole, 2-undecylimidazole, 2-phenylimidazole, 1,2-dimethylimidazole, and 2,4-diamino-6-[2'-methylimidazolyl-(1')]ethyl-s-triazine; salts of the imidazole compound and trimellitic acid such as 1-cyanoethyl-2-phenylimidazolium trimellitate; salts of the imidazole compound and isocyanuric acid; salts of the imidazole compound and hydrobromic acid. The imidazole compound and its derivatives may be used alone or in combination of two or more. The curing accelerator may be an imidazole compound or a derivative thereof, or may be an imidazole compound.

[0038] When the thermosetting resin composition contains a curing accelerator, the content thereof is preferably 0.1 to 20 parts by mass, and more preferably 0.1 to 10 parts by mass, based on 100 parts by mass of the thermosetting resin.

[0039] (Inorganic filler) The inorganic filler can reduce the thermal expansion coefficient and improve the strength of the coating film. Examples of inorganic fillers include silica, alumina, barium sulfate, talc, mica, kaolin, boehmite, beryllia, barium titanate, potassium titanate, strontium titanate, calcium titanate, aluminum carbonate, magnesium hydroxide, aluminum hydroxide, aluminum borate, aluminum silicate, calcium carbonate, calcium silicate, magnesium silicate, zinc borate, zinc stannate, aluminum oxide, zirconia, mullite, magnesia, zinc oxide, titanium oxide, silicon carbide, silicon nitride, boron nitride, clay (e.g., calcined clay, etc.), molybdic acid compounds such as zinc molybdate, glass short fibers, glass powder, and hollow glass beads. Examples of glass, which is a material for glass short fibers, glass powder, and hollow glass beads, include E glass, T glass, and D glass. One type of inorganic filler may be used alone, or two or more types may be used in combination. Among these, silica and alumina are preferred from the viewpoint of reducing the thermal expansion coefficient, the dielectric constant and the dielectric loss tangent, and aluminum hydroxide is preferred from the viewpoint of heat resistance, and a combination of silica and aluminum hydroxide is more preferred as the inorganic filler. Examples of the silica include precipitated silica produced by a wet method and having a high water content, and dry method silica produced by a dry method and containing almost no bound water, etc. Dry method silica further includes crushed silica, fumed silica, and fused silica (fused spherical silica) depending on the production method. The inorganic filler may be surface-treated with a surface treatment agent such as a silane coupling agent in order to improve moisture resistance, and may be hydrophobized in order to improve dispersibility.

[0040] When the thermosetting resin composition contains an inorganic filler, the content of the inorganic filler varies depending on the purpose of addition, but is preferably 0.1 to 65% by volume relative to the total solid content. If the content is 0.1% by volume or more, the thermal expansion coefficient tends to be small. On the other hand, by suppressing the content to 65% by volume or less, the viscosity during blending of the resin components does not become too high, and it tends to be easy to suppress the deterioration of workability. From the same viewpoint, the content of the inorganic filler is more preferably 10 to 60% by volume, further preferably 15 to 55% by volume, and particularly preferably 30 to 55% by volume relative to the total solid content.

[0041] (Coupling Agent) The inclusion of a coupling agent has the effect of improving the dispersibility of the inorganic filler and the organic filler, and improving the adhesion to the reinforcing substrate and the metal foil. The coupling agent may be used alone or in combination of two or more kinds. The coupling agent may be a titanate coupling agent, a silane coupling agent, or the like.

[0042] (Organic solvent) From the viewpoint of facilitating handling, the thermosetting resin composition may further contain an organic solvent. In the present disclosure, the thermosetting resin composition containing an organic solvent may be referred to as a resin varnish. The organic solvent is not particularly limited, but examples thereof include alcohol-based solvents such as methanol, ethanol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, butanone, cyclohexanone, and 4-methyl-2-pentanone; ester-based solvents such as ethyl acetate, butyl acetate, propylene glycol monomethyl ether acetate, and γ-butyrolactone; ether-based solvents such as tetrahydrofuran; aromatic solvents such as toluene, xylene, and mesitylene; nitrogen-containing solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; and sulfur-containing solvents such as dimethyl sulfoxide. The organic solvent may be used alone or in combination of two or more kinds.

[0043] From the viewpoint of ease of application, for example, the content of the organic solvent may be adjusted so that the solid content concentration of the thermosetting resin composition is preferably 20 to 85 mass %, more preferably 40 to 80 mass %. However, although a resin varnish may be prepared using an organic solvent, the prepreg is obtained through a process of producing a resin film and then impregnating the resin film into a fiber substrate, and therefore the organic solvent volatilizes during the resin film production stage. As a result, almost no organic solvent remains in the prepreg, specifically 5 mass % or less.

[0044] The method for preparing the thermosetting resin composition is not particularly limited, and any conventionally known preparation method can be used. For example, a thermosetting resin and other components as necessary are added to the organic solvent, and then the mixture is mixed and stirred using various mixers to prepare a resin varnish. Examples of the mixer include ultrasonic dispersion type, high-pressure collision type dispersion type, high-speed rotation dispersion type, bead mill type, high-speed shear dispersion type, and rotation-revolution type dispersion type mixers.

[0045] (Prepreg manufacturing method) As the method for producing the prepreg, the following method is preferable from the viewpoint of improving the thickness accuracy of the metal-clad laminate. In other words, a method for producing a prepreg is preferred in which a film of a thermosetting resin composition is impregnated into a fiber base material having a thickness of 40 μm or more by lamination, and a surface waviness (Wa) of 5.0 μm or less is achieved by providing impregnated areas and unimpregnated areas of the thermosetting resin composition in the fiber base material. In this production method, a film of a thermosetting resin composition (hereinafter, sometimes referred to as a "resin film") is used. In the method for producing the prepreg, the fiber base material, the thermosetting resin composition, and the surface waviness (Wa) are as described above.

[0046] The resin film can be produced by forming a layer of a thermosetting resin composition (hereinafter, sometimes abbreviated as a resin layer) on one side of a support. The resin layer can be formed, for example, by applying the resin varnish to one side of the support and then drying it. The film produced in this manner is sometimes called a resin film with a support. The method of applying the resin varnish is not particularly limited, and can be carried out using a known coating device such as a comma coater, a bar coater, a kiss coater, a roll coater, a gravure coater, a die coater, etc. It is preferable to appropriately select these coating devices depending on the film thickness of the resin layer. The drying temperature and drying time will vary depending on the amount of organic solvent used, the boiling point of the organic solvent, etc., but for example, in the case of a resin varnish containing 30 to 70 mass % of an organic solvent, a resin film can be suitably formed by drying at 50 to 160°C for 1 to 8 minutes.

[0047] (Thickness of resin film) The thickness of the resin film may be appropriately determined depending on the thickness of the prepreg, etc. For example, when the thickness of the fiber substrate is in the range of 40 to 120 μm, the thickness of the resin film is preferably 10 to 100 μm, more preferably 15 to 70 μm, and even more preferably 20 to 50 μm. In the present disclosure, the thickness of the resin film is a value measured as follows. First, the total thickness of the resin-attached film after coating is measured using a Digimatic indicator at any five points. The resin layer at the measurement points is peeled off with an adhesive tape, and the thickness of the support is measured using a Digimatic indicator, and the average value of the values ​​obtained by subtracting the thickness of the support from the total thickness is obtained. When the thickness of the resin film is equal to or greater than the lower limit, a sufficient amount of resin for impregnating a thick glass cloth having a thickness of 40 μm or more tends to be secured. When the thickness of the resin film is equal to or less than the upper limit, the resin film tends to be easily produced.

[0048] (Support) Examples of the support include organic films such as polyethylene terephthalate (PET), biaxially oriented polypropylene (OPP), polyethylene, polyvinyl fluoride, and polyimide; metal foils of metals such as copper and aluminum, or alloys thereof, etc. These supports may be treated with a release agent for release. The thickness of the support is not limited, and from the viewpoints of ease of handling when applying the thermosetting resin composition and economic efficiency, it is preferably 10 to 200 μm, more preferably 20 to 100 μm, and even more preferably 30 to 70 μm. As the support, a commercially available product can be used.

[0049] (Method of impregnating a fiber substrate with a resin film) Next, a method for impregnating the fiber base material with the resin film by lamination will be described. First, the resin film with the support is placed on at least one surface of the fiber substrate so that the resin film is in contact with the fiber substrate. Then, the resin film with the support and the fiber substrate are heated and pressurized to impregnate the fiber substrate with the resin film. At this time, an area not impregnated with the thermosetting resin composition is provided in the fiber substrate. In this way, a prepreg with a support is obtained. The heating and pressure application here is preferably carried out by lamination, which can be performed by (a) roll lamination or (b) a method of laminating under reduced pressure such as vacuum lamination.

[0050] (a) The conditions for roll lamination are not particularly limited, but from the viewpoint of providing an area not impregnated with the thermosetting resin composition, the heating temperature is preferably 80 to 180° C., and the applied pressure (linear pressure) is preferably 0.05 to 1.0 MPa / m. (b) The conditions for the method of laminating under reduced pressure are not particularly limited, but from the viewpoint of providing an area not impregnated with the thermosetting resin composition, the heating temperature is preferably 50 to 170°C, and more preferably 100 to 160°C, the vacuum time is preferably 10 to 120 seconds, and more preferably 20 to 80 seconds, the pressurization time is preferably 10 to 120 seconds, and more preferably 20 to 80 seconds, and the pressurization pressure is preferably 0.05 to 1.0 MPa, and more preferably 0.1 to 0.6 MPa.

[0051] (Method of Providing Unimpregnated Region) The method for providing the fiber substrate with the non-impregnated region of the thermosetting resin composition is not particularly limited, but may be, for example, a method of adjusting the conditions for heating and pressing the supported resin film and the fiber substrate, specifically, a method of adjusting the lamination conditions. Here, when the lamination conditions are the same for the thin fiber substrate and the thick fiber substrate, the thick fiber substrate tends to be more difficult to impregnate the resin film into the fiber substrate. Therefore, even if the lamination conditions of this embodiment are the same as those of the conventional thin fiber substrate, the fiber substrate can have an unimpregnated region of the thermosetting resin composition. Specific methods for adjusting the heating and pressurizing conditions are not particularly limited, but include, for example, the following methods. First, a prepreg is prepared under a predetermined heating and pressing conditions, and then the ratio of the impregnated region of the thermosetting resin composition in the fiber base material is calculated based on the calculation method. As a result, if the impregnated region is 100%, that is, if there is no unimpregnated region, the heating temperature or the pressurizing pressure is lowered, or both the heating temperature and the pressurizing pressure are lowered, the prepreg is reprepared, and the ratio of the impregnated region is calculated again. By repeating this process as necessary, the conditions for producing a prepreg having an unimpregnated region can be easily grasped. When it is desired to adjust the proportion of unimpregnated regions to a lower value, the heating temperature or the pressing pressure may be increased, or both the heating temperature and the pressing pressure may be increased, and the prepreg may be produced again. When lamination is performed under reduced pressure, it is also possible to adjust the proportion of unimpregnated regions by adjusting the degree of vacuum.

[0052] It is preferable to laminate one or more resin films on each side of the fiber substrate. The number of resin films per side of the fiber substrate is preferably one or two, and more preferably one. After the resin film has been impregnated into the fiber base material, it is cooled as necessary, and then the support is peeled off from the resulting prepreg with the support, thereby producing a prepreg with a surface waviness (Wa) of 5.0 μm or less.

[0053] [Printed wiring board] The present disclosure also provides a printed wiring board containing the metal-clad laminate of this embodiment. The printed wiring board of this embodiment is a printed wiring board obtained by forming a wiring pattern on the metal-clad laminate of this embodiment. In other words, the printed wiring board of this embodiment does not need to contain the metal-clad laminate of this embodiment as it is, and a wiring pattern may be formed on the metal-clad laminate, or the top and bottom of the insulating resin layer (the cured product of one or more prepregs) may be in a conductive state through via holes opened in the metal-clad laminate. Examples of the method for forming the wiring pattern include known methods such as a subtractive method, a full-additive method, a semi-additive method (SAP: Semi Additive Process), and a modified semi-additive method (m-SAP: modified Semi Additive Process). If necessary, a multi-layered adhesive process can be carried out to produce a multi-layered printed wiring board. In the printed wiring board of the present embodiment, the prepreg and the resin film are C-staged. In the present disclosure, C-staged refers to a state of C-stage defined by JIS K6900 (1994).

[0054] [Semiconductor package] The present disclosure also provides a semiconductor package including the printed wiring board of the present embodiment and a semiconductor element. The semiconductor package of the present embodiment can be manufactured, for example, by mounting a semiconductor element such as a semiconductor chip or memory at a predetermined position of the printed wiring board of the present embodiment by a known method, and then sealing the semiconductor element with a sealing resin or the like. EXAMPLES

[0055] The present embodiment will now be described in more detail with reference to the following examples, but these examples are not intended to limit the present embodiment. The prepregs, copper-clad laminates, and semiconductor packages produced in the respective examples were measured and evaluated according to the following methods.

[0056] [1. Surface waviness (Wa)] Using a shape analysis laser microscope "VK-X100" (manufactured by Keyence Corporation), the shape of the prepreg produced in each example was automatically measured using an observation application, and a waviness curve conforming to ISO 4287 (1997) was obtained. For the obtained waviness curve, a surface roughness analysis was performed using an analysis application, and the surface waviness (Wa) of the prepreg was calculated. Here, the waviness curve is a curve obtained by applying a phase compensation high-pass filter λc (λc = 80 μm) to the cross-sectional curve and removing wavelengths less than 80 μm from the cross-sectional curve. The analysis range was 1,000 μm x 1,000 μm. The surface waviness (Wa) was measured on both sides of the prepreg, and the larger value was used.

[0057] [2. Ratio of impregnated regions] The ratio (%) of the region impregnated with the thermosetting resin composition in the fiber base material of the prepreg produced in each example was determined based on the following calculation method. -Calculation method- The surface of the prepreg was observed under the following conditions using an optical microscope (manufactured by Olympus Corporation, product name: MX61L-F) to obtain a surface observation image. <Observation conditions> ·Magnification: 50x Observation mode: dark field Sensitivity: ISO400 Exposure time for surface photography: 60-100ms - Brightness of the observation environment: Two 35W fluorescent lamps were installed 2m above the observation stage. The obtained surface observation image was converted to black and white mode using image editing software, and then saved in BMP (Microsoft Windows Bitmap Image) format. Next, the black and white mode surface observation image saved in BMP format was converted to RGB (Red, Green, Blue) values ​​for each pixel using image conversion software, and then saved in CSV (comma-separated values) format. The RGB data saved in CSV format was pasted into Microsoft Excel (Microsoft Corporation), and the areas of the black parts (RGB value = 255) and white parts (RGB value = 0) were calculated. From these values, the area ratio of the black parts to the total of the black and white parts was calculated. The area ratio of the black parts thus obtained was taken as the presence ratio (%) of the impregnated region. Here, when photographing the surface observation image, the image was photographed at an appropriate brightness by adjusting the exposure time during surface photographing between 60 and 100 ms as described above so that the impregnated and non-impregnated areas could be adequately reflected. The image editing software used was "Microsoft Paint" (manufactured by Microsoft Corporation), and the image conversion software used was "bmp2csv," which is free software.

[0058] [3. Thickness of copper clad laminate] Four measurement substrates (N1 to N4) measuring 60 mm length x 60 mm width in the surface direction were cut out from the four corners of the copper-clad laminate produced in each example (see FIG. 7). The thicknesses of the four measurement substrates were measured using a non-contact and clamp-type laser displacement meter "CL-3000 series (sensor head: CL-L015)" (multi-color laser coaxial displacement meter, manufactured by Keyence Corporation) under the following conditions: measurement speed; 10 mm / sec, measurement range; diameter 300 μm, resolution; 0.003 μm, repeatability accuracy 0.3 μm or less, and sensor head size (arrow part in Figure 3); diameter 26 mm. The thickness was measured at 1 mm intervals on two diagonals, with the start and end points of the measurement not being located at the ends of the metal-clad laminate, as shown in Figure 1. As a result, 84 points were measured on each diagonal, and the thickness was measured at 168 points in the surface direction of the copper-clad laminate (however, even if there were overlapping measurement points on the diagonal measurement lines, each was counted as one point). For each of the four measurement boards (N1 to N4), the standard deviation (σ value) was calculated from the thickness of the 168 measured points, and then the average value of the standard deviation (σ value) of the thickness for each of the four measurement boards (the sum of the standard deviation of the thickness of each of the four measurement boards / 4) was calculated. Furthermore, the average thickness of all the measured points for N1 to N4 was calculated, and this was taken as the average thickness of the copper-clad laminate. In addition, these numerical values ​​were used to determine the value obtained by the following formula (1). Formula (1): (Average value of standard deviation (σ value) of thickness obtained by the above measurement method) × 100 / (average thickness of copper-clad laminate)

[0059] [4. Variation in dimensional change rate of copper-clad laminate] Two copper-clad laminates were prepared for each example, and two of each were cut into 340 mm × 250 mm pieces (four in total) to be used as evaluation boards, as shown in Figure 8. A total of four reference holes were made in each of the four evaluation boards, 1 cm vertically and 1 cm horizontally from the four corners, and the distance between adjacent holes was measured using a CNC image measuring machine (manufactured by Mitutoyo Corporation, product name: QV-H606T1L-D), and this value was used as the "reference dimension." The evaluation board thus obtained was immersed in a copper etching solution (type of chemical solution: ammonium persulfate, temperature: 40° C., treatment time: 5 minutes) to remove the copper foil from the evaluation board. Next, the evaluation board from which the copper foil had been removed by etching was heated in air at 180° C. for 1 hour, then allowed to cool to 25° C., and heated again in air at 180° C. for 1 hour. Thereafter, the distance between adjacent holes was measured using the same method as above, and this value was taken as the "dimension after heating." From the dimensions obtained above, the dimensional change rate after heating was calculated for the four evaluation substrates based on the following formula. Dimensional change rate (%) = (dimension after heating - reference dimension) x 100 / reference dimension After calculating the dimensional change rate of the four evaluation substrates (two data in the vertical direction and two data in the horizontal direction per substrate), the standard deviation (σ value) was calculated and used as an index of the variation in the dimensional change rate. The variation in the dimensional change rate is preferably 0.005% or less.

[0060] [5. Variation in the amount of warpage in semiconductor packages] As shown in FIG. 7, four pieces of 60 mm×60 mm were cut out from the four corners of the copper-clad laminate produced in each example, and each was used as a core substrate. A substrate having the following layer structure (rectangle with an outer dimension of 60 mm x 60 mm in plan view) was produced on both sides of one of the core substrates using build-up material (manufactured by Ajinomoto Co., Inc., product name "GX92", thickness 30 μm) (hereinafter also referred to as "BU"), copper foil (manufactured by Mitsui Mining & Smelting Co., Ltd., product name "3EC-M3-VLP", thickness 12 μm), and solder resist (manufactured by Resonac Inc., product name "SR-7300") (hereinafter also referred to as "SR"), and a total of four similar substrates were produced. (Layer structure of the substrate) SR / Copper foil (Remaining copper rate 65%) / BU / BU / Copper foil (Remaining copper rate 100%) / BU / BU / Copper foil (Remaining copper rate 100%) / BU / BU / Core board / BU / BU / Copper foil (Remaining copper rate 100%) / BU / BU / Copper foil (Remaining copper rate 100%) / BU / BU / Copper foil (Remaining copper rate 65%) / SR

[0061] In the above substrate, the thickness of the SR was 20 μm, the radius of the solder resist opening was 100 μm, and pads with a pad diameter of 150 μm and a pad pitch of 200 μm were provided.

[0062] Each layer was laminated in the following order (1) to (5). (1) Two sheets of build-up material were laminated on each side of the metal-clad laminate obtained in each example, and copper foil was placed on the exposed surfaces of the build-up materials on both sides, and then the laminate was press-molded under conditions of 180°C, 0.5 MPa, and 90 minutes. (2) Two sheets of build-up material were further laminated on each side of the obtained laminate, and copper foil was placed on the exposed surfaces of the build-up materials on both sides, followed by press molding under the same conditions as above. (3) The same operation as in (2) above was carried out, and two build-up materials and copper foil were further laminated on both sides. (4) The copper foil on both sides of the laminate obtained in (3) above was etched to obtain a predetermined pattern. (5) On both sides of the laminated plate that had been subjected to the above step (4), a solder resist layer having predetermined openings was formed using the above solder resist.

[0063] Next, a silicon semiconductor chip was mounted in the center of one side of the substrate obtained above. The semiconductor chip was mounted by bonding the bumps on the circuit side of the semiconductor chip to the pads of the substrate using the TCB (Thermal Compression Bonding) method. The configuration of the semiconductor chip is as follows: (Configuration of semiconductor chip) Chip size: 25mm x 25mm rectangular in plan view, thickness 0.725mm Bump pitch: 200μm Bump metal: Sn-Ag solder alloy on Cu pillar Bump height: Cu pillar; 45μm, Sn-Ag solder alloy; 15μm Bump size: diameter 90μm

[0064] Thereafter, the gap between the semiconductor chip and the substrate was sealed with a liquid sealing material (manufactured by Resonac Corporation, product name "CEL-C-3730 series") to obtain a semiconductor package. The same operation was carried out for all four substrates, to produce a total of four semiconductor packages. The maximum warpage of each of the four semiconductor packages obtained above was measured at 25° C. and 260° C. using a warpage measuring device (manufactured by Akrometrix, product name "Thermoray") The heating rate was 20° C. per minute. Next, the average value for the four semiconductor packages was calculated from the maximum warpage at 25℃ and 260℃, and the standard deviation (σ value) for the average value was calculated and used as an index of variation in the warpage of the semiconductor packages. The standard deviation (σ value) was rounded off to the first decimal place and listed in Table 1. It can be said that the smaller the standard deviation (σ value), the smaller the variation in the amount of warpage of the semiconductor package. The standard deviation (σ value) is preferably 10 μm or less, more preferably 8 μm or less, and even more preferably 6 μm or less.

[0065] The glass cloth used in each example is shown below. (i) Glass cloth "IPC#2116" (manufactured by Nitto Boseki Co., Ltd., basis weight: 104 g / m 2 , substrate width: 530mm, thickness: 91μm) (ii) Glass cloth "IPC#2118" (manufactured by Nitto Boseki Co., Ltd., basis weight: 112 g / m 2 , substrate width: 530mm, thickness: 92μm) The thickness of each glass cloth was determined by averaging values ​​obtained by measuring five arbitrary points with a micrometer "MDC-25MX" (manufactured by Mitutoyo Corporation).

[0066] Manufacturing Example 1 (Preparation of Resin Varnish A) 60 parts by mass of phenol novolac type epoxy resin "EPICLON (registered trademark) N-770" (manufactured by DIC Corporation, epoxy equivalent: 188 g / eq), 40 parts by mass of biphenyl aralkyl type phenol resin (manufactured by Meiwa Kasei Co., Ltd., product name: MEH-7700), 17.5 parts by mass of aluminum hydroxide, 86 parts by mass of fused silica, 0.5 parts by mass of 2-methylimidazole, and methyl isobutyl ketone and cyclohexanone as dilution solvents were added and mixed to prepare resin varnish A with a solids concentration of 65% by mass (aluminum hydroxide content: 8% by volume, fused silica content: 32% by volume).

[0067] Manufacturing Example 2 (1. Preparation of modified maleimide resin) 595.8 g of bis(4-maleimidophenyl)methane, 54.2 g of 4,4'-diaminodiphenylmethane, and 350.0 g of propylene glycol monomethyl ether were placed in a 2 L reaction vessel equipped with a thermometer, a stirrer, and a moisture meter with a reflux condenser, and the mixture was allowed to react for 5 hours under reflux to obtain a solution of a modified maleimide resin (solid concentration: 65% by mass). (2. Preparation of Resin Varnish B) 107 parts by mass of the modified maleimide resin solution, 30 parts by mass of tetrafunctional naphthalene-type epoxy resin "EXA-4710" (DIC Corporation), 17.5 parts by mass of aluminum hydroxide, 130 parts by mass of fused silica, 0.5 parts by mass of 2,4-diamino-6-[2'-undecylimidazolyl-(1)']-ethyl-S-triazine, and methyl isobutyl ketone and cyclohexanone as dilution solvents were added and mixed to prepare resin varnish B with a solids concentration of 65% by mass (aluminum hydroxide content: 8% by volume, fused silica content: 41.5% by volume).

[0068] Example 1 (1. Preparation of resin film) The resin varnish A obtained in Production Example 1 was applied onto a PET film (manufactured by Toray Industries, Inc., thickness: 50 μm, product name: S10) using a comma coater. At this time, the amount of application was adjusted so that the application width was 530 mm and the thickness after drying was 30 μm. Thereafter, a resin film with a PET film was produced by heating and drying at 130° C. for 2 minutes. (2. Preparation of prepreg) Next, a glass cloth "IPC#2116" (manufactured by Nitto Boseki Co., Ltd., basis weight: 104 g / m) with a length of 530 mm and a width of 530 mm was used. 2 The resin film with the PET film was placed on both sides of a glass cloth (substrate width: 530 mm, thickness: 91 μm) so that the resin layer surface of the resin film with the PET film was in contact with the glass cloth. This laminate of "PET film / resin film / glass cloth / resin film / PET film" was heated and pressed under vacuum using a vacuum laminating device. In this way, a prepreg with a PET film was obtained in which the glass cloth was impregnated with the thermosetting resin composition of the resin film. The conditions for the vacuum lamination were a hot plate temperature of 130° C., a pressure of 0.5 MPa, a degree of vacuum of 100 kPa or less, a vacuum time of 30 seconds, and a heating time of 30 seconds. The PET film was peeled off from the obtained prepreg with the PET film to obtain prepreg 1 (thickness 125 μm). The thickness of the prepreg 1 was determined as the average value of the values ​​measured at any five points using a horizontally adjusted base and a Digimatic Indicator (manufactured by Mitutoyo Corporation). The content ratio of the thermosetting resin composition in prepreg 1 was calculated as follows. The mass of the resin film (w r The mass of the resin film (w r ) and the mass of prepreg 1 (w p ) was used to calculate the content of the thermosetting resin composition according to the following formula. Content of thermosetting resin composition (mass%)=(w r / w p ) x 100 The above-mentioned measurements were also carried out on the obtained prepreg 1. The results are shown in Table 1. The surface observation image of the prepreg converted into black and white mode, which was used in calculating the abundance ratio of the impregnated region, is shown in Figure 6. The observation conditions for the prepreg surface were as described above, but the exposure time for photographing the surface was 85 ms. (3. Preparation of copper-clad laminate) Twelve sheets of the obtained prepreg 1 were stacked, and 12 μm thick copper foil "GTS-12" (manufactured by Furukawa Electric Co., Ltd.) was placed on top and bottom of them. Then, pressing was performed under the following conditions, and the end of the obtained copper-clad laminate was cut to produce a copper-clad laminate 1 having a size of 500 mm × 500 mm. The obtained copper-clad laminate 1 was subjected to the above-mentioned measurements and evaluations. The results are shown in Table 1. -Press conditions- Heating conditions (resin varnish A): The temperature was raised from 25° C. to 185° C. at a rate of 3° C. / min, and the temperature was maintained at 185° C. for 90 minutes, followed by cooling for 30 minutes. Pressure conditions (pressure applied to 12 prepregs sandwiched between copper foils): 4MPa (from the start of heating to the end of cooling)

[0069] Example 2 A copper-clad laminate 2 was produced in the same manner as in Example 1, except that the number of prepreg layers was changed to 6 in the production of the copper-clad laminate of Example 1, and the above-mentioned measurements and evaluations were carried out. The results are shown in Table 1.

[0070] Example 3 In the preparation of the prepreg of Example 1, prepreg 3 (thickness 120 μm) was prepared by carrying out the same operation as in Example 1 except that, in the vacuum lamination conditions, the hot plate temperature was changed to 140° C., the vacuum time was changed to 50 seconds, and the heating time was changed to 50 seconds. In addition, in the production of the copper-clad laminate of Example 1, prepreg 3 was used instead of prepreg 1, and the number of prepreg layers was changed to 14. In addition, in the production of the copper-clad laminate of Example 1, copper-clad laminate 3 was prepared by carrying out the same operation as in Example 1. The above-mentioned measurements and evaluations were carried out for the prepreg 3 and the copper-clad laminate 3. The results are shown in Table 1.

[0071] Example 4 In the preparation of the prepreg of Example 1, the hot plate temperature was changed to 150°C under the vacuum lamination conditions, but the same operation as in Example 1 was performed to prepare prepreg 4 (thickness 115 μm). In addition, in the production of the copper-clad laminate of Example 1, prepreg 4 was used instead of prepreg 1, and the number of prepreg layers was changed to 6, but the same operation as in Example 1 was performed to prepare copper-clad laminate 4. The above-mentioned measurements and evaluations were performed on the prepreg 4 and the copper-clad laminate 4. The results are shown in Table 1.

[0072] Example 5 In the production of the resin film of Example 1, resin varnish B was used instead of resin varnish A, and in the production of the prepreg, the conditions of vacuum lamination were changed to 150 ° C., the pressure bonding pressure was changed to 0.7 MPa, the vacuum time was changed to 60 seconds, and the heating time was changed to 60 seconds. Except for this, prepreg 5 (thickness 110 μm) was produced by performing the same operation as in Example 1. In addition, in the production of the copper-clad laminate of Example 1, prepreg 5 was used instead of prepreg 1, and the pressing conditions were changed as follows. Copper-clad laminate 5 was produced by performing the same operation as in Example 1. The above-mentioned measurements and evaluations were performed on the prepreg 5 and the copper-clad laminate 5. The results are shown in Table 1. -Press conditions- Heating conditions (resin varnish B): The temperature was raised from 25° C. to 230° C. at a rate of 3° C. / min, and the temperature was kept at 230° C. for 90 minutes, followed by cooling for 30 minutes.

[0073] Example 6 In the preparation of the resin film of Example 1, the PET film was changed to (manufactured by Toray Industries, Inc., thickness: 50 μm, support, product name: Lumirror (registered trademark) #50-X44), and resin varnish B was used instead of resin varnish A. Except for this, prepreg 6 (thickness 125 μm) was prepared by the same operation as in Example 1. In addition, in the production of the copper-clad laminate of Example 1, prepreg 6 was used instead of prepreg 1, the number of prepreg layers was changed to 6, and the pressing conditions were changed as follows. Copper-clad laminate 6 was prepared by the same operation as in Example 1. The evaluation results of prepreg 6 and copper-clad laminate 6 are shown in Table 1. -Press conditions- Heating conditions (resin varnish B): The temperature was raised from 25° C. to 230° C. at a rate of 3° C. / min, and the temperature was kept at 230° C. for 90 minutes, followed by cooling for 30 minutes.

[0074] Example 7 In the preparation of the prepreg of Example 3, the glass cloth "IPC#2116" was replaced with the glass cloth "IPC#2118" (manufactured by Nitto Boseki Co., Ltd., basis weight: 112 g / m 2 Prepreg 7 (thickness 120 μm) was produced by carrying out the same operations as in Example 3, except that the dimensions of the laminate were changed to 530 mm (base material width: 530 mm, thickness: 92 μm) and the hot plate temperature in the vacuum lamination conditions was changed to 145° C. In addition, copper-clad laminate 7 was produced by carrying out the same operations as in Example 3, except that prepreg 7 was used instead of prepreg 3 in the production of the copper-clad laminate of Example 3. The evaluation results of prepreg 7 and copper-clad laminate 7 are shown in Table 1.

[0075] Example 8 In the preparation of the prepreg of Example 5, the glass cloth "IPC#2116" was replaced with the glass cloth "IPC#2118" (manufactured by Nitto Boseki Co., Ltd., basis weight: 112 g / m 2Prepreg 8 (thickness 130 μm) was produced by carrying out the same operation as in Example 5, except that the conditions of vacuum lamination were changed to a hot plate temperature of 110° C., a pressure bonding pressure of 0.3 MPa, a vacuum time of 20 seconds, and a heating time of 20 seconds. In addition, in the production of the copper-clad laminate of Example 5, prepreg 8 was used instead of prepreg 5, and the number of laminated prepregs was changed to 6. Copper-clad laminate 8 was produced by carrying out the same operation as in Example 5. The results of the measurements and evaluations of prepreg 8 and copper-clad laminate 8 are shown in Table 1.

[0076] Comparative Example 1 Glass cloth "IPC#2116" (manufactured by Nitto Boseki Co., Ltd., basis weight: 104 g / m 2 A copper-clad laminate X (thickness: 180 μm) was produced by immersing a copper-clad laminate (base material width: 530 mm, thickness: 91 μm) in the resin varnish A prepared in Production Example 1, removing it, and drying it by heating at 140° C. for 3.5 minutes. The copper-clad laminate X was produced by carrying out the same operations as in Example 1, except that prepreg X was used instead of prepreg 1 in the production of the copper-clad laminate of Example 1. The results of the measurements and evaluations of prepreg X and copper-clad laminate X are shown in Table 1. In addition, since prepreg X had a large surface waviness, the prepreg surface was not in focus during optical microscope observation, and the proportion of impregnated regions could not be determined.

[0077] Comparative Example 2 Copper-clad laminate Y was produced by carrying out the same operations as in Comparative Example 1, except that the number of prepreg layers was changed to 6 in the production of the copper-clad laminate of Comparative Example 1. The results of the measurements and evaluations of the prepreg Y and the copper-clad laminate Y are shown in Table 1. The results are shown in Table 1.

[0078] [Table 1]

[0079] From Table 1, it can be seen that the copper-clad laminates produced in the examples have an average thickness of 400 μm or more, and the value calculated by the formula (1) is 0.70% or less, and the semiconductor packages produced using these have small variations in the amount of warpage. In addition, the copper-clad laminates also have small variations in the rate of dimensional change after etching and heat treatment. On the other hand, the copper-clad laminate produced in the comparative example had a value calculated by the above formula (1) exceeding 0.70%, and it is found that the semiconductor package produced using this tends to have a large variation in the amount of warpage. In addition, the copper-clad laminate also tended to have a large variation in the rate of dimensional change after etching and heat treatment.

Claims

1. A metal-clad laminate including three or more fiber base materials having a metal foil and three or more cured prepregs, the prepregs having an impregnated region and an unimpregnated region of the thermosetting resin composition in the fiber base material, A metal-clad laminate having an average thickness of 400 μm or more as measured using a laser displacement meter according to the following method, a value calculated from the following formula (1) of 0.70% or less, and a thickness of a fiber base material located on the outermost side on at least one surface side of the metal-clad laminate being within a range of 0.6 to 1.3 times the thickness of a fiber base material adjacent to the fiber base material. Formula (1): (average value of standard deviation of thickness obtained by the method described below) × 100 / (average thickness of metal-clad laminate) (Method of measuring thickness of metal-clad laminate) The thickness is measured by cutting out four measurement substrates, each measuring 60 mm long x 60 mm wide in the surface direction, from any point on the metal-clad laminate. Measurements are performed at 1 mm intervals on two diagonals, with the start and end points of the measurement not being located at the ends of the metal-clad laminate. For each of the four test substrates, the standard deviation is calculated from the thicknesses at all the measured points, and then the average value of the standard deviations of the thicknesses for each of the four test substrates is calculated. Furthermore, the average thickness of all the measured points for the four test substrates is calculated, and this is regarded as the average thickness of the metal-clad laminate.

2. The metal-clad laminate according to claim 1, wherein the average value of the standard deviation of the thickness in the formula (1) is 0.1 to 10.0 μm.

3. 2. The metal-clad laminate according to claim 1, wherein the prepreg is a prepreg containing a fiber base material having a thickness of 40 μm or more and a thermosetting resin composition.

4. 2. The metal-clad laminate according to claim 1, wherein the average thickness of the metal-clad laminate measured according to the above method is 1,000 μm or more.

5. The metal-clad laminate according to claim 1, wherein the metal foil has a thickness of 1 to 200 μm.

6. A printed wiring board comprising the metal-clad laminate according to claim 1.

7. A semiconductor package comprising the printed wiring board according to claim 6 and a semiconductor element.

Citation Information

Patent Citations

  • High heat resistance laminate which uses poly 4-methyl-1-pentene, and its application

    JP2006015727A

  • Method for producing prepreg, prepreg, metal-clad laminate, and printed wiring board

    JP2010248520A

  • Prepreg, metal-clad laminate, and printed wiring board

    JP2015189834A

  • Resin composition, and printed wiring board, laminated sheet, and prepreg using same

    WO2012099134A1

  • Metal-clad layered plate production method, metal-clad layered plate, printed circuit board and semiconductor package, and coreless base board forming support and semiconductor re-wiring layer forming support

    WO2020144861A1